2018
DOI: 10.1371/journal.pone.0192340
|View full text |Cite
|
Sign up to set email alerts
|

Chronic morphine exposure potentiates p-glycoprotein trafficking from nuclear reservoirs in cortical rat brain microvessels

Abstract: The rates of opioid prescription and use have continued to increase over the last few decades resulting in a greater number of opioid tolerant patients. Treatment of acute pain from surgery and injury is a clinical challenge for these patients. Several pain management strategies including prescribing increased opioids are used clinically with limited success; all currently available strategies have significant limitations. Many opioids are a substrate for p-glycoprotein (p-gp), an efflux transporter at the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Various methods have been established to model morphine withdrawal in rats including implantation of morphine pellet (55, 56, 69-71), infusion method via implantation of intravenous catheters (72,73), subcutaneous mini osmatic pumps (74,75), drinking morphine solution containing water or sucrose (76)(77)(78), morphine-admixed food (79), or subcutaneous injection (80)(81)(82)(83) and intraperitoneal route (54, 84,85). However, all these methods have certain disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been established to model morphine withdrawal in rats including implantation of morphine pellet (55, 56, 69-71), infusion method via implantation of intravenous catheters (72,73), subcutaneous mini osmatic pumps (74,75), drinking morphine solution containing water or sucrose (76)(77)(78), morphine-admixed food (79), or subcutaneous injection (80)(81)(82)(83) and intraperitoneal route (54, 84,85). However, all these methods have certain disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…The combined effect of MOR and CP was even further increase in hepatic P-gp level in the current study. Previous studies investigated the effect of MOR and/or CP on P-gp expression in the blood-brain barrier [37][38][39], and reported that both CP and MOR might up-regulate P-gp in this sanctuary barrier, causing efflux of the latter and decrease in its central penetration, and consequently, decrease in its analgesic efficacy. Up-regulation of P-gp by CP was not reported to be limited to normal body cells, but extended to include tumor cells [33], where P-gp was related to MDR of cancer cells against chemotherapeutic [40], especially when using P-gp substrates as anticancer drugs concomitantly with CP.…”
Section: Discussionmentioning
confidence: 99%
“…In order to study the impact of NMO-IgG on BBB structure itself, we use an original ex vivo BBB mimicking the close relationship between NMO-IgG and brain microvessels. Fresh IBM are known to maintain in vivo BBB properties, and have been previously used for the study of endothelial molecular transporters [31,32], drug pharmacokinetic or pharmacodynamics [33], and disease pathophysiology in animal models [34,35]. However, the application of this technique on NMOSD-related models has not been previously performed.…”
Section: Discussionmentioning
confidence: 99%